Unpacking Caregiver Experiences in Positive Deviance Hearth Programs: Facilitators and Barriers to Sustainable Child Nutrition Interventions in Kenya - Gladys Chemutai Koskei; Simon Karanja; Zipporah W. Ndungu; Calvince Otieno Anino (Utan Kayu Publishing, 2026)
Child undernutrition remains a major and persistent public health problem in Kenya, especially among children under five years of age, despite the implementation of evidence-based community nutrition interventions. The positive deviance hearth programs have demonstrated effectiveness in rehabilitating and improving short-term nutritional outcomes through leveraging locally available foods and positive dietary or caregiving behaviors. However, caregivers' lived experiences and perspectives and factors influencing the sustainability of gains achieved after completion of PDH programs have remained underexplored, with no published evidence yet. The study aimed to fill this research gap by exploring caregivers’ experiences and perspectives regarding perceived barriers and facilitators of sustaining improved child nutrition practices following a six-month positive deviance hearth intervention conducted in Konoin Sub-County, Bomet county, Kenya, from July to August 2025. A qualitative exploratory study was conducted after completion of the PDH intervention in Bomet County among caregivers of children under five years involved in the program. Focused group discussions and in-depth interviews were conducted until thematic saturation was achieved. Discussions and interviews were audio-recorded, transcribed verbatim, coded, and inductive reflexive thematic analysis. NVivo version 14 software used in data analysis. A total of fourteen FDGs and IDIs were conducted. The discussions and interviews revealed two main major themes and several linked sub-themes: (i) facilitating factors (including improved nutrition knowledge and caregiving practices, observable child well-being improvement, and peer learning and community motivation) and (ii) barriers (such as food insecurity and economic limitations, caregiver workload and competing domestic roles, and cultural beliefs and intra-household resistance). The findings highlight that PDH programs are perceived as supportive in promoting nutrition knowledge, positive caregiving behaviors, and motivation to sustain improved practices. However, persistent food insecurity, economic constraints, competing household responsibilities, and cultural resistance were experienced as key barriers to adoption and sustainability of PDH-recommended practices. Therefore, integrating economic, social, and community-based support mechanisms and sustained community engagement is critical for sustaining post-PDH child nutrition practices.